2022
DOI: 10.1111/ijlh.13978
|View full text |Cite
|
Sign up to set email alerts
|

Development and exacerbation of autoimmune hemolytic anemia following COVID‐19 vaccination: A systematic review

Abstract: Autoimmune hemolytic anemia (AIHA) is caused by the production of autoantibodies against RBCs. COVID‐19 vaccines can reduce the risk of severe disease, however, various adverse effects such as AIHA were observed following vaccination. This review aimed to assess the relationship of AIHA and COVID‐19 vaccination using the PRISMA guidelines. Among 18 cases included in this review, new post‐vaccination AIHA development was reported in 11 patients (7 women and 4 men) with a median age of 67.0 years. In 7 of 11 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…6,7,9,10,12,1517,19–21 Coagulation defects risk increased with both mRNA vaccine and viral vector vaccine, with no difference in risk between the two vaccines. While hemolytic anemia has been reported following COVID-19 vaccination, 17,23,26 especially with mRNA vaccines, 17,23,26 our study found that the incidence of hemolytic anemia was low in the COVID-19 vaccine recipient group, regardless of the vaccine type. This suggests the need for further research to confirm the mechanisms between COVID-19 vaccine components and RBC antibodies in a larger population.…”
Section: Discussioncontrasting
confidence: 57%
“…6,7,9,10,12,1517,19–21 Coagulation defects risk increased with both mRNA vaccine and viral vector vaccine, with no difference in risk between the two vaccines. While hemolytic anemia has been reported following COVID-19 vaccination, 17,23,26 especially with mRNA vaccines, 17,23,26 our study found that the incidence of hemolytic anemia was low in the COVID-19 vaccine recipient group, regardless of the vaccine type. This suggests the need for further research to confirm the mechanisms between COVID-19 vaccine components and RBC antibodies in a larger population.…”
Section: Discussioncontrasting
confidence: 57%
“…Treatment options given include corticosteroids, RBC transfusions and rituximab. [12] In this study, one out of the three AIHA patients did improve with administration of corticosteroids; the majority had incomplete data.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, the mounting reports of these life-threatening sequelae are alarming, and further investigation of the underlying pathophysiology as well as adverse event monitoring and correlation with phenotypic associations are needed. Notably, we did not identify any reports of AIHA, thrombotic thrombocytopenic purpura, or acquired coagulation factor inhibitors in the VAERS database, all of which have been reported in association with the original formulations of the Pfizer-BioNTech and Moderna vaccines [6,7,12,13]. However, we acknowledge that one limitation of VAERS is that it is a passive reporting system, which may contribute to underreporting, therefore biasing the calculated rate and prevalence of reported conditions.…”
Section: Discussionmentioning
confidence: 93%
“…While observed following all vaccine types, VITT is most commonly associated with the Ad26.COV2.S (Johnson & Johnson/Janssen) and ChAdOx1 nCoV-19 (AstraZeneca) adenoviral vector vaccines [4]. ITP [5] and AIHA [6,7] have also been reported following SARS-CoV-2 vaccination, including among patients vaccinated with the mRNA-1273 (Moderna) and BNT162b2 (Pfizer-BioNTech) vaccines at low rates.…”
Section: Introductionmentioning
confidence: 99%